EMPLOYEE ENGAGEMENT DAN BUDAYA ORGANISASI PENGARUHNYA TERHADAP KINERJA KARYAWAN - Fachri, Saeful; Suharno Suharno; Cecep Warman (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of employee engagement and organizational culture on the employee performance of PT Marga Mandalasakti.The research employs an explanatory approach witha quantitative methodology. Data were collected through questionnaires and the sampling technique used was saturated sample, involving 41 employes as respondents.Data analysiswas conducted using quantitative analytical methods. The results of the descriptive analysis indicate that the level of employee enggament and organizational culture exhibits a positive and significant effect on employee performance. In contrast, organizational culture exhibits a positive and significant influenceon performance. Simultaneouslyboth variabel-employee enggamnet and organizational culture postively and significanly affect the employee performance at PT Marga Mandalasakti